EFEKTIVITAS TEKNIK ALEXANDER DALAM PEMBELAJARAN OLAH VOKAL DI EKSTRAKURIKULER SMAN 1 BANJARSARI - Anisa Trie Febian; Dadang Dwi Septiyan; Alis Triena Permanasari (MATRA: Jurnal Seni Musik Tari Teater & Rupa, 2026)
This study aims to determine the effectiveness of the Alexander Technique in vocal learning at extracurricular activities in SMAN 1 Banjarsari. Problems identified in the field indicated that students were unable to properly apply diaphragmatic breathing, had poor posture while singing, and experienced tension in the neck, shoulders, and jaw that hindered sound production. This study employed a quantitative method with a One Group Pretest-Posttest experimental design conducted over four sessions. The research subjects consisted of 10 active members of the vocal extracurricular. The instrument comprised 10 practical vocal tasks covering five assessment aspects: diaphragmatic breathing, articulation and intonation, visual awareness, relaxation and tension reduction, and body posture. The results showed that the average score increased from 29.3 in the pretest to 51.1 in the posttest. The Paired Sample T-Test yielded a significance value of 0.00 ≤ 0.05, proving that the Alexander Technique effectively improved students' vocal skills both technically and expressively in the extracurricular program at SMAN 1 Banjarsari. Keywords: Alexander Technique, effectiveness, vocal training, diaphragmatic breathing, extracurricular